CONCEPTUAL-METHODOLOGICAL BASIS OF NATIONAL EDUCATION IN FORMING THE PEDAGOGICAL SKILLS OF FUTURE PRIMARY TEACHERS (Eureka Journal of Education & Learning Technologies, 2026)
This article analyzes the conceptual and methodological foundations of national education in forming the pedagogical skills of future primary teachers. During the study, the influence of national values, folk pedagogy, ethnopedagogical approaches and value-based pedagogical technologies on the development of pedagogical skills was studied. The study used theoretical analysis, comparative analysis, observation, pedagogical experiment-testing and statistical methods. The results showed that pedagogical approaches based on national education are effective in developing the communicative, reflexive and axiological competencies of future primary teachers. The results of the study substantiate the need to introduce innovative methods based on national education in the pedagogical higher education system.
Keywords: National education, pedagogical skills, ethnopedagogy, primary education, future teacher, pedagogical competence, values, reflexive approach, axiological competence, folk pedagogy.